PENGELOLAAN DANA DESA DI KECAMATAN GUNTUR: PERSPEKTIF FRAUD DIAMOND THEORY - Mukhlas Adi Putra; Nugroho Tulus Rahayu; Sarbullah . Sarbullah (JURNAL STIE SEMARANG, 2020)
The field study was used in this study to test the diamond cheating theory presented by Wolf and Hermanson as a means of detecting fraud in the use of the village budget in villages in Guntur Subdistrict, Demak Regency. The theoretical contribution of this research as information and consideration for related parties in managing the village budget. This theory results from the development of fraud triangle theory developed by Cressey's with the addition of the capability element. The village head and all his apparatus in the Guntur District as the population in this study. Each village 10 respondents were taken as the study sample. The results found that the pressure and opportunity variables did not significantly influence fraud detection. Variation rationalization and capability significantly influence the detection of fraud in the use of village funds in Guntur District. The limitation of this study is that the object of the research is different from previous studies, where the respondents are actors in the use of village budget funds in Guntur District